TR14 Innovative ways of working… staying within a reduced budget!. (November 2018) - Nicklin, Jane
Abstract : Background: In 2017, I led on a project to procure a diverse range of clinical, educational and simulation equipment to facilitate the move of a small, more traditional clinical skills centre on a university campus to their new state-of-the-art dedicated Centre for Clinical Skills and Simulation. The initial equipment budget was £3 76 560 Summary of education programme or project: Such significant expenditure was attributed to the transfer to a new building, a proportion of developing University programmes and/or the increase in teaching space and student numbers. However, there was also an urgent need for the University to catch up with the ever-increasing growth in the use of simulation technologies to ensure that the education of all healthcare professionals in their university was fit-for-purpose. Within the first six months of the project, the budget was reduced by 30%, an action that brought considerable challenges requiring both shrewd negotiating and innovative thinking. Five approaches were taken to keep within the reduced budget: Sourcing of refurbished, used equipment from reputable companies Capitalisation on relationships built up over a period of time with simulation equipment companies and sales representatives to gain substantial discounts and complimentary items/accessories, these ranged from 2% up to 25% with some complimentary items Maximise the Universities eligibility for VAT zero-rating Offer specific, appropriate items for funding and/or donations Identify redundant or replaced equipment in Leven for resale Summary of results: Several unforeseen events arose during procurement, however, these were suitably managed to stay within the constraints of the budget, for example, there were some discrepancies in the original quotes and estimates due to validity and the timespan, also any carriage and/or delivery charges were not in the initial calculations However, all items required to furnish and operationalise the new Centre for Clinical Skills and Simulation were purchased within budget Discussion, conclusions and recommendations: Both the facility and faculty are now suitably equipped to offer and deliver quality, simulation-based education to their healthcare students in an environment that truly reflects the clinical area, the next phase will need to include the plan for providing training on the functionality of all the new equipment. Reference: Aggarwal R, Mytton OT, Derbrew M, et al. Training and simulation for patient safety. BMJ Quality & Safety2010;19:i34–i43.